Lower cross syndrome: specific treatment protocol versus generalized treatment protocol. A randomized single-blinded trial - Trupti B. Mehta; Amit Sharma (Folia Medica)
Introduction: Lower crossed syndrome (LCS) is a biomechanical muscle imbalance causing low back pain. Aim: This study aimed to compare specific treatment protocols versus generalized treatment protocols for managing low back pain associated with LCS. Materials and methods: This randomized, single-blinded trial involved 200 patients (aged 20-40 years) with low back pain and LCS. Patients were divided into four groups: A1 and A2 (specific protocols for posterior and anterior LCS), and B1 and B2 (generalized protocols). Interventions were administered thrice weekly for two weeks. Outcome measures included Numerical Pain Rating Scale (NPRS), Modified Oswestry Disability Questionnaire (MODQ), Lumbar Lordosis Index (LLI), abdominal and gluteal muscle strength, and iliopsoas and back extensor flexibility. Results: All groups showed significant improvements in all parameters (p<0.01). However, specific protocols demonstrated superior outcomes. Group A1 showed the greatest reductions in pain (median NPRS decrease: 5), disability (median MODQ decrease: 45), iliopsoas tightness (median decrease: 12°) and back extensor tightness (median decrease 6.5). Group A2 exhibited the highest improvements in abdominal strength (median increase: 8 kg) and gluteal muscle strength (median increase: 8 kg). Conclusion: Specific treatment protocols were significantly more effective than generalized protocols in managing low back pain associated with LCS. These findings emphasize the importance of accurate LCS classification and tailored interventions for optimal therapeutic outcomes in patients with low back pain.